Exploration of Sports Participation and Curriculum Resource Utilization in Primary Schools Before and After the “Double Reduction” - Liu, Shuhong; Wang, Guihong (Frontiers in Psychology, 2022)
The purpose is to eliminate capital chaos in the Education And Training (EAT) industry and ease parents' and students' excessive attention to subject achievements over physical quality. The state has launched the "Double Reduction" ("DR") policy to promote students' Sports Participation (SP) in the Compulsory Education (CE) stage concerning students' physical and mental health. Firstly, based on the actual situation of students' SP before and after releasing the "DR" policy, this paper understands the exact needs of parents and children. Secondly, following empirical research and mathematical statistics, it analyzes the structure and characteristics of students' SP before and after the release of the "DR" policy. Mainly, the experiment focuses on the frequency, project types, and off-campus class expenditure. It also considers students' SP motivation in on-campus and off-campus sports classes before and after the "DR" policy proposal. Eventually, the strategies are put forward to optimize students' SP under the "DR" from the perspectives of family, school, and society. The results show that after the release of "DR," parents and schools gradually pay attention to student's physical health and better understand students' physical exercise in school. The consumption expenditure on sports off-campus classes has increased significantly. Meanwhile, family income and the father's occupation significantly impact the children's SP frequency in off-campus sports classes. Overall, "DR" is a protracted war. The existing difficulties need to be solved by families, schools, and the government. The research provides a practical basis for extending and managing on-campus sports classes and training. It helps timely uncover the problems in policy implementation. It guides the formulation of PE policy in the next stage of CE.